2022
DOI: 10.14710/jkm.v10i3.33186
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Jenis Kelamin, Umur, Dan Aktivitas Fisik Dengan Diabetes Melitus Tipe 2 Pada Lansia Di Puskesmas Balaraja Kabupaten Tangerang

Abstract: Type 2 diabetes mellitus is the most common type of diabetes accounting for 90% of all diabetes in the world is type 2 diabetes mellitus. Indonesia is ranked 7th out of 10 countries in the world. From health service data, the prevalence of people with type 2 diabetes mellitus has increased with a prevalence of 14.47% in 2019. This study aims to determine the relationship between sex, age, and physical activity with type 2 diabetes mellitus in the elderly at the Balaraja Health Center, Tangerang Regency. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Lack of physical activity can also result in a decline in body condition and make a person susceptible to disease (12). This research is not in line with research conducted by Rosita R (2022) (13), who stated that there is no relationship between physical activity and the incidence of type 2 Diabetes Mellitus. Physical activity is a protective factor against the incidence of type 2 DM.…”
Section: Discussioncontrasting
confidence: 95%
“…Lack of physical activity can also result in a decline in body condition and make a person susceptible to disease (12). This research is not in line with research conducted by Rosita R (2022) (13), who stated that there is no relationship between physical activity and the incidence of type 2 Diabetes Mellitus. Physical activity is a protective factor against the incidence of type 2 DM.…”
Section: Discussioncontrasting
confidence: 95%
“…In line with researchPutu et al, (2015)said this growth in understanding was the result of health education and health information [16], [17] The results of the study of the two groups found that the highest proportion was in female respondents where there were differences in sex characteristics, namely women. According to research [18]there is a relationship between gender and type 2 diabetes mellitus in elderly women because women are more likely to gain weight and hormonal changes cause fat to accumulate in post-menopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the research conducted by Rosita, Kusumaningtiar, Irfandi, and Ayu (2022) at the Balaraja Health Center, Tangerang Regency, where a p = 1,000 value was obtained, it can be concluded that there is no relationship between physical activity and DM. Physical activity is a body movement that requires energy.…”
Section: Frequency Distribution Based On Diagnosed Diabetes Mellitusmentioning
confidence: 93%